2021
DOI: 10.1038/s41557-021-00830-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium conditions inside rock pores drive fission, maintenance and selection of coacervate protocells

Abstract: Key requirements for the first cells on Earth include the ability to compartmentalize and evolve. Compartmentalization spatially localizes biomolecules from a dilute pool and an evolving cell, which, as it grows and divides, permits mixing and propagation of information to daughter cells. Complex coacervate microdroplets are excellent candidates as primordial cells with the ability to partition and concentrate molecules into their core and support primitive and complex biochemical reactions. However, the evolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 37 publications
0
73
0
Order By: Relevance
“…Such spatial control over reactions can determine resulting patterns [126,127] and localize droplets [128,129]. Finally, the interplay between bulk and surface dynamics implies a prominent role of geometry, which was described in detail for traditional reaction-diffusion systems, like the Min oscillations [130,131], but could also control droplets, e.g., at the origin-of-life [132]. Spatially patterned catalysts could provide detailed control over the kinetics of chemical reactions, which in turn affect where droplets form.…”
Section: Interaction With the Environmentmentioning
confidence: 98%
“…Such spatial control over reactions can determine resulting patterns [126,127] and localize droplets [128,129]. Finally, the interplay between bulk and surface dynamics implies a prominent role of geometry, which was described in detail for traditional reaction-diffusion systems, like the Min oscillations [130,131], but could also control droplets, e.g., at the origin-of-life [132]. Spatially patterned catalysts could provide detailed control over the kinetics of chemical reactions, which in turn affect where droplets form.…”
Section: Interaction With the Environmentmentioning
confidence: 98%
“…[119] However, there is recent experimental evidence in its favor. [120] Li et al proposed a new model of solid protocells in the form of self-assembled graphene capsules containing selective ion channels. [121] It was reported that on these capsules, the L-amino acids exhibited higher reactivity than D-amino acids to form peptides, and under the influence of graphene the peptides would be transformed into a secondary structure, promoting the synthesis of left-handed proteins.…”
Section: Inorganic Compartmentsmentioning
confidence: 99%
“…[141] Following a theoretical study on how chemically active droplets grow and divide, [153] gas bubbles inside heated rock cavities were shown to promote the growth, fusion, division and selection of coacervate microdroplets consisting of polyanionic (carboxymethyl dextran, ATP) and polycationic (poly (diallyl dimethyl ammonium chloride), poly (l-lysine)) species. [120] Between coacervates and lipidic protocells exists a considerable range of membranous and membrane-like structures that can form an interface. Membrane material of such interfacial assemblies can consist of inorganic nanoparticles, proteins, amphiphilic block copolymers, or mixtures of bio-macromolecules and polyelectrolytes.…”
Section: Coacervatesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the atmospheric composition (and subsequently, density) may be significantly different from that of Earth, while the gravitational forces on the recipient planet may also result in differences in entry velocities, both of which could result in lower entry temperatures for an M‐BPS onto a recipient planet and increase its survivability. Additionally, it can not be ruled out that an M‐BPS could have arrived on a recipient planet enclosed within or co‐assembled rocks, landmasses, or other minerals (similar to those investigated recently such as clay microparticle‐containing droplets [ 163 ] or membraneless droplets within rock pores [ 200 ] ), that is, lithopanspermia, which could have also resulted in protection of both the M‐BPS and/or encapsulated components from decay. Thus, although a gel‐based M‐BPS may not easily survive entry into the Earth's atmosphere, some fraction of M‐BPS may still survive entry into another atmosphere‐containing receiving planet.…”
Section: Open Questions and Limitation To The Material‐based Pansperm...mentioning
confidence: 99%